Correlation between Carotid Blood Flow Velocity and Total Magnetic Resonance Imaging Burden of Cerebral Small Vessel Disease in Patients with Recent Small Subcortical Infarcts - Lv, Yi-Jun; Zhang, Qing-Xiu; LI, Jing-Wei; Yun, Wen-Wei; Zhang, Min (Current Neurovascular Research, 2023)
Background: The common and internal carotid arteries are the upstream vessels of the small cerebral vessels. The relationship between hemodynamic changes in the significant cervical vessels and cerebral small vessel disease (CSVD) remains uncertain. This research sought to analyze the correlation between carotid blood flow velocity and the total magnetic resonance imaging (MRI) burden of CSVD in patients with recent small subcortical infarcts (RSSIs). Methods: Data were gathered from individuals diagnosed with RSSIs admitted to Changzhou Second People's Hospital between January 2022 and June 2023. Brain MRI was performed on every patient to determine the overall MRI burden of CSVD, along with carotid duplex ultrasound to evaluate carotid blood flow velocity and pulsatility index (PI) of the common carotid (CCA) and internal carotid (ICA) arteries. The association between carotid blood flow velocity and the total MRI load of CSVD was examined using univariate and multivariate analyses. Results: For our investigation, 272 individuals with RSSIs were screened. 82 individuals had a moderate to severe load of CSVD, while 190 participants showed a mild burden. Patients with moderate to severe burden of CSVD had lower end-diastolic velocity (EDV) and higher PI in CCA and ICA than those with mild load (P < 0.001). After adjusting for variables like age, hypertension, systolic blood pressure, and blood homocysteine levels, multivariate logistic regression analysis showed that EDV in CCA (OR, 0.894; P = 0.011), PI in CCA (OR, 5.869; P = 0.017), EDV in ICA (OR, 0.909; P = 0.008), and PI in ICA (OR, 5.324; P = 0.041) were independently related to moderate to severe CSVD burden. Spearman correlation analysis showed that EDV in CCA and ICA was negatively related to the total MRI load of CSVD in patients with RSSIs (P < 0.001). PI in CCA and ICA was positively associated with the whole MRI load of CSVD (P < 0.001). Conclusion: Low carotid blood flow velocity and high carotid pulsatility index are independently associated with moderate to severe burden of CSVD.
Keywords: pulsatility index